Understanding the Roles of Electrogenerated Co3+ and Co4+ in Selectivity‐Tuned 5‐Hydroxymethylfurfural Oxidation - Deng, Xiaohui; Xu, Ge‐Yang; Zhang, Yue‐Jiao; Wang, Lei; Zhang, Jiujun; Li, Jian‐Feng; Fu, Xian‐Zhu; Luo, Jing‐Li (Angewandte Chemie International Edition, 2021)
The Co‐based electrocatalyst is among the most promising candidates for electrochemical oxidation of 5‐hydroxymethylfurfural (HMF). However, the intrinsic active sites and detailed mechanism of this catalyst remains unclear. We combine experimental evidence and a theoretical study to show that electrogenerated Co3+ and Co4+ species act as chemical oxidants but with distinct roles in selective HMF oxidation. It is found that Co3+ is only capable of oxidizing formyl group to produce carboxylate while Co4+ is required for the initial oxidation of hydroxyl group with significantly faster kinetics. As a result, the product distribution shows explicit dependence on the Co oxidation states and selective production of 5‐hydroxymethyl‐2‐furancarboxylic acid (HMFCA) and 2,5‐furandicarboxylic acid (FDCA) are achieved by tuning the applied potential. This work offers essential mechanistic insight on Co‐catalyzed organic oxidation reactions and might guide the design of more efficient electrocatalysts. A detailed mechanism for cobalt‐catalyzed electrochemical 5‐hydroxymethylfurfural (HMF) oxidation is revealed. A combined experimental and theoretical study shows that a Co3+ species is capable of oxidizing the formyl group to produce carboxylate but remains inert towards oxidation of the hydroxyl group. In contrast, a Co4+ species is required for the initial oxidation of the hydroxyl group in HMF.